A case of Solitary fibrous pleura tumor associated with severe hypoglycemia: the Doege-Potter 's Syndrome - Haddoub, Silvia; Gnetti, L; Montanari, A; Di Ruvo, R; Carbognani, P; Maccanelli, F; Magotti, M. G.; Calderini, M. C.; Cioni, Federico; Tardio, S. M. (Acta Biomedica Atenei Parmensis, 2017)
Solitary fibrous pleura tumor is a rare primary intrathoracic tumor of the pleura. It usually has an indolent clinical course, but sometimes it can have an aggressive behaviour. In 1930 Doege and Potter independently described this neoplasm, presenting with symptoms of hypoglycemia, hence the eponim of Doege-Potter’s Syndrome. In this report, we illustrate a case of Doege Potter’s Syndrome, treated with complete surgical resection.